2015
DOI: 10.1016/j.ccell.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Somatic Mutations Converge on the Cell Cycle and Define Similar Evolutionary Histories in Brain Tumors

Abstract: Summary The evolutionary history of tumor cell populations can be reconstructed from patterns of genetic alterations. In contrast to stable genetic events, epigenetic states are reversible and sensitive to the microenvironment, prompting the question whether epigenetic information can similarly be used to discover tumor phylogeny. We examined the spatial and temporal dynamics of DNA methylation in a cohort of low-grade gliomas and their patient-matched recurrences. Genes transcriptionally upregulated through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
206
3
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(243 citation statements)
references
References 56 publications
25
206
3
9
Order By: Relevance
“…Analysis of ITH in gliomas (Mazor et al, 2015) as well as prostate cancers (Aryee et al, 2013) and esophageal squamous cell carcinomas (Hao et al, 2016) has suggested that the extent of ITH calculated from DNA methylation mirrors ITH measures captured at the genomic level.…”
Section: How Much Heterogeneity Is There?mentioning
confidence: 99%
“…Analysis of ITH in gliomas (Mazor et al, 2015) as well as prostate cancers (Aryee et al, 2013) and esophageal squamous cell carcinomas (Hao et al, 2016) has suggested that the extent of ITH calculated from DNA methylation mirrors ITH measures captured at the genomic level.…”
Section: How Much Heterogeneity Is There?mentioning
confidence: 99%
“…Segregating clones based on the presence of independent or shared mutations has revealed part of the tumor development process (27)(28)(29)(35)(36)(37). The clonal evolution model posits that tumor formation is initiated in a cell of origin and is followed by the accumulation of single or multiple somatic genetic alterations, leading to advantages in survival or growth (38).…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…The fittest cell populations likely establish precancerous clones, although we have little direct evidence to support this process in human GBM because of limitations in detecting the early steps in brain cell transformation (42,43). Divergent genetic alterations in early transformed cells can subsequently give rise to a variety of clones under the selective pressure of the evolutionary ecosystem in the tumor (27)(28)(29)(35)(36)(37). A cell's spatial location in the tumor is related to its divergent genomic profile, and clones with similar types of genetic alterations are more proximal to each other than those with dissimilar profiles (Figure 1B and refs.…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 For instance, patients with IDH mutation showed hypermethylation of the CpG island and increased histone demethylation. [22][23][24] IDH converts isocitrate to a-ketoglutarate (a-KG) during normal TCA cycle, whereas mutant IDH converts a-KG to D-2-hydroxyglutarate (D-2HG) in an NADPH-dependent manner that has been associated with secondary GBM. [22][23][24][25][26] Nonetheless, 4 independent cases of MRI-classified SVZassociated GBM used in this study do not contain IDH mutation (Fig.…”
Section: Mri-classified Svz-associated Gbm Has Alteration Of Epigenetmentioning
confidence: 99%